THE INFLUENCE OF WORK DISCIPLINE AND WORK LOYALTY ON EMPLOYEE PERFORMANCE AT THE BATUJAJAR DISTRICT OFFICE - Anggraeni, Reni; Kadarisman, Sumeidi; Mulyani , Sri Rochani (Multifinance, 2026)
The Batujajar District Office, as a government institution, is expected to provide optimal public services. In achieving this, employee performance is the main determinant of organizational success. However, challenges related to work discipline and employee loyalty remain obstacles in achieving maximum performance. This study was conducted at the Batujajar District Office with the aim of determining the Effect of Work Discipline and Work Loyalty on Employee Performance, both partially and simultaneously. This study used a descriptive verification method with a quantitative approach. The results of the study indicated that work discipline and work loyaltu have a pesitive influence on employee performance. Of the two, work loyalty has a more dominant influence, at 58%, compared to work discipline, which contributed 21%. The coefficient of determination (R2) of 0,790 indicates that these two variables collectively contribute 79% to employee performance, while the remaining 21% is due to other factors not examined in this study. Based on these findings, improved employee performance can be achieved through continuous strengthening of work loyalty.